Old game, new rules? The dynamics of enterprise bargaining under the Fair Work Act. (February 2017) - Pekarek, Andreas; Landau, Ingrid; Gahan, Peter; Forsyth, Anthony; Howe, John
Over the last quarter century, enterprise bargaining has evolved to be a primary mechanism through which wages and conditions of employment are determined in Australia. Since the introduction of the Fair Work Act, the process for negotiating enterprise agreements has been governed by principles of good faith bargaining. There has been considerable debate over the potential for these provisions to change the dynamics of bargaining, yet empirical evidence of these effects remains limited. This article reports on a field study investigating the experiences of industrial parties negotiating enterprise agreements during the first three years of the Fair Work Act . Drawing on the tribunal's own case management database, along with a large sample of interviews, the study provides a more systematic examination of the extent to which the parties have deployed the new principles governing collective bargaining, with a particular focus on good faith provisions, and whether these principles have altered the dynamics of bargaining practices.